ENGLISH TEACHERS’ STRATEGIES TO TRAIN STUDENTS’ CRITICAL THINKING SKILLS - Persada Zuhri, Fuji; Eki Saputra; Kiagus Baluqiah; Ririn Putri Ananda (Teaching English and Language Learning English Journal, 2025)
The objectives of this study are to investigate the strategies used by English teachers to train students' critical thinking skills and to investigate the most dominant strategy used by English teachers to train students' critical thinking skills at SMAN 1 Bengkulu Utara. The design of this research was a descriptive qualitative research. The population of this research were three English teachers who teach English at SMAN 1 Bengkulu Utara. The English teachers were qualified as professional teachers who have been taught English for more than five years. All of the population above became the sample of this research. In order to collect the data for this study, the researcher employed observation checklist and interview as the instruments of this research. The instruments of this research were designed by theory of Bean (2011) who divided nine strategies in critical thinking, namely; the problem-posing strategy, the frame strategy, the question-generating strategy, the believing and doubting strategy, the evidence-finding strategy, the case strategy, the norming session strategy, the “rough draft workshop” strategy, and the metacognitive strategy. This research found that the teachers implemented six strategies. All of the teachers implemented The Problem-Posing Startegy, the Question-Generating Strategy, The Believing And Doubting Strategy, and The Evidence-Finding Strategy. Thirty three percent of the norming session strategy and the metacognive strategy. There was no teacher who implemented the frame strategy, the case strategy, and the “Rough Draft Workshop” strategy. Moreover, the dominant startegies implemented by the teachers to train students’ critical thinking were the Problem-Posing Startegy, the Question-Generating Strategy, the Believing And Doubting Strategy, and the Evidence-Finding Strategy. Keywords: English Teacher, Strategies, Critical Thinking Skilss